Bilateral Diffuse Fluorodeoxyglucose Uptake in Thyroid Gland Diagnosed by Fluorodeoxyglucose-Positron Emission Tomography/Computed Tomography - Win, Aung; Aparici, Carina (World Journal of Nuclear Medicine, 2014)
Our patient is a female who was first diagnosed with breast cancer at the age of 23. A follow-up fluorodeoxyglucose-positron emission tomography/computed tomography (FDG-PET/CT) at age 44 revealed diffuse high FDG uptake in an enlarged thyroid gland. Fine-needle aspiration (FNA) of the thyroid mass revealed estrogen receptor/progesterone receptor negative, human epidermal growth factor receptor 2+ breast cancer. To the best of our knowledge, this is the first case to report breast cancer metastasis to the thyroid in a diffuse pattern on FDG-PET/CT. Bilateral diffuse uptake of FDG in thyroid is the most commonly associated with benign conditions. However, FNA biopsies need to be done to rule out metastatic disease in thyroid lesions with diffuse high FDG uptake, especially for patients with history of cancer.
Keywords: Breast cancer; diffuse; fluorodeoxyglucose-positron emission tomography/computed tomography; metastasis; thyroid